Keefektifan Jenis dan Konsentrasi Insektisida Botanis dalam Mengendalikan Hama Phaedonia inclusa Stall pada Tanaman Kacang Hijau - Helly Laurette Tanasale (Fakultas Pertanian, Universitas Pattimura, 2020)
Phaedonia inclusa Stall pest attack is an important issue in mung bean production because of its potentialdamages resulted. Application of botanical insecticide in pest management was widely known as a rightchoice in terms of its less harmful effect to environment and human compare to synthetic insecticide. Theaims of this research were to explore the nature and effective concentration of botanical insecticide tocombat Phaedonia inclusa pest on mung bean. The research was done by using factorial experimentarranged into completely block designs with two factors namely factor A (kind of botanical insecticide)and factor B (concentration of botanical insecticide). The results showed that a mixture of 25 g of Aeglemarmelos Corr fruit extraction in 100 ml water was found more effective to control Phaedonia inclusapest on mung bean in comparison to Datura metel leaf and Piper betle leaf mixture.